Analisis Sastra Siber Puisi Apa Guna Karya Widji Thukul dalam Platform Youtube dengan Pendekatan Ekspresif - Eva Nurhasanah; Rahayu Utami (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This research was motivated by the author's admiration for Widji Thukul's work and the author's interest in analyzing one of the poems as an extraordinary work because there are many meanings that need to be studied. The purpose of this research is to analyze the cyber literature of Widji Thukul's poem “Apa Guna” in YouTube platform with Expressive Approach. The research method used in this research is descriptive qualitative method, which is a method used to describe the condition of the object naturally, in detail, and systematically at an exclusive time; as well as to find insights, with the researcher as the main instrument in the research. The result of the analysis stated that the cyber literature in the Hyperlink of poem “Apa Guna” by Widji Thukul presented in YouTube platform can be connected with other platforms, such as X, Instagram, Facebook, Whatsapp, and TikTok; and its Hypertext can be connected with poems “Air Kendi”, “Sajak Anak Muda”, “Buku Itu Cahaya”, “Di Negerimu”, “Satu Saat dalam Sejarah”, “Awas”, ‘Soliloquy’, “Menempuh Jalan Rakyat”, “Tanah Sunda”, and poem “Surat Ini Adalah Sebuah Sajak Terbuka”. In the development of technology, the poem “Apa Guna” by Widji Thukul remains relevant to the current situation, both in terms of presentation and the content and meaning of the poem itself. With the literary expressive approach, this poem expresses Widji Thukul's anger, annoyance, and disappointment towards the intellectuals and the rulers, as well as his concern and empathy towards the helpless common people. This is reflected in the diction used in each line of his poem. In the cyber literary context of the poem “Apa Guna”, Hyperlinks and Hypertext help to expand and emphasize the meaning of the poem with inter-platform links and interlinks between other poetry texts.